Effectiveness of various health education media on behavior changes of Indonesian teenagers: Literature Review - Halim, Elwina Meylentia (BKM Public Health and Community Medicine, 2021)
Objective: Although the use of media in health education and counseling has been widely studied in Indonesia, most of them are limited to its effect on knowledge and attitude changes. Knowledge and attitude variables alone are not enough to improve the quality of health, particularly in the adolescent population. Aside from the limited number of studies examining the influence of media on behavior changes, a literature review that discusses various types of media comprehensively is also needed to design an evidence-based health education and promotion program for adolescents. Therefore, this literature review aims to compare the effect of various health education media on the behavior changes of adolescents in Indonesia. Method: A literature search was carried out systematically with related keywords through an electronic database limited to the year 2015-2020 in Indonesia. Effectiveness was analyzed by seeing the p-value, as well as comparing results between before and after the intervention, as well as between intervention groups. Results: Booklets were proven to be effective, while leaflets were less effective compared to video or audiovisual media. The use of more than one type of media (multimedia) can increase the effectiveness of health education. Conclusions: Policymakers and health actors should consider the type of media carefully when designing health promotion and education programs for adolescents. Media with comprehensive information content that involves more than one type of sense is more effective to encourage health behavior changes among adolescents in Indonesia. Keywords: health education; media; adolescent; behavior